NAD+ Metabolism, Metabolic Stress, and Infection - Groth, Benjamin; Venkatakrishnan, Padmaja; Lin, Su-Ju (Frontiers in Molecular Biosciences, 2021)
Nicotinamide adenine dinucleotide (NAD+) is an essential metabolite with wide-ranging and significant roles in the cell. Defects in NAD+ metabolism have been associated with many human disorders; it is therefore an emerging therapeutic target. Moreover, NAD+ metabolism is perturbed during colonization by a variety of pathogens, either due to the molecular mechanisms employed by these infectious agents or by the host immune response they trigger. Three main biosynthetic pathways, including the de novo and salvage pathways, contribute to the production of NAD+ with a high degree of conservation from bacteria to humans. De novo biosynthesis, which begins with L-tryptophan (TRP) in eukaryotes, is also known as the kynurenine (KYN) pathway. Intermediates of this pathway have various beneficial and deleterious effects on cellular health in different contexts. For example, dysregulation of this pathway is linked to neurotoxicity and oxidative stress. Activation of the de novo pathway is also implicated in various infections and inflammatory signaling. Given the dynamic flexibility and multiple roles of NAD+ intermediates, it is important to understand the interconnections and cross-regulations of NAD+ precursors and associated signaling pathways to understand how cells regulate NAD+ homeostasis in response to various growth conditions. Although regulation of NAD+ homeostasis remains incompletely understood, studies in the genetically tractable budding yeast Saccharomyces cerevisiae may help provide some molecular basis for how NAD+ homeostasis factors contribute to the maintenance and regulation of cellular function and how they are regulated by various nutritional and stress signals. Here we present a brief overview of recent insights and discoveries made with respect to the relationship between NAD+ metabolism and selected human disorders and infections, with a particular focus on the de novo pathway. We also discuss how studies in budding yeast may help elucidate the regulation of NAD+ homeostasis.